1992
DOI: 10.1096/fasebj.6.14.1426767
|View full text |Cite
|
Sign up to set email alerts
|

Transcription by RNA polymerase II: initiator‐directed formation of transcription‐competent complexes 1

Abstract: Studies of transcription by RNA polymerase II have revealed two promoter elements, the TATA motif and the initiator (Inr), capable of directing specific transcription initiation. Although binding to the TATA motif by one of the components of the transcription machinery has been shown to be the initial recognition step in transcription complex formation, many promoters that lack a traditional TATA motif have recently been described. In such TATA-less promoters, the Inr element is critical in positioning RNA pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
248
3
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 391 publications
(265 citation statements)
references
References 65 publications
13
248
3
1
Order By: Relevance
“…Fmr1 along with gene family members fragile X related gene 1 and 2 (Fxr1 and Fxr2) are highly conserved among vertebrates (Zhang et al, 1995). The Fmr1 gene contains a TATA-less promoter region and three initiator-like sequences that correspond to three transcription start sequences (Weis and Reinberg, 1992;Chow et al, 1995). The CpG island of the promoter region of Fmr1 is affected by the CGG trinucleotide expansion and through a poorly understood mechanism promotes the deacetylation of histones, possibly in an effort to halt the CGG expansion ( Figure 1; Richards et al, 1993).…”
Section: The Fragile X Mental Retardation Gene and Proteinmentioning
confidence: 99%
“…Fmr1 along with gene family members fragile X related gene 1 and 2 (Fxr1 and Fxr2) are highly conserved among vertebrates (Zhang et al, 1995). The Fmr1 gene contains a TATA-less promoter region and three initiator-like sequences that correspond to three transcription start sequences (Weis and Reinberg, 1992;Chow et al, 1995). The CpG island of the promoter region of Fmr1 is affected by the CGG trinucleotide expansion and through a poorly understood mechanism promotes the deacetylation of histones, possibly in an effort to halt the CGG expansion ( Figure 1; Richards et al, 1993).…”
Section: The Fragile X Mental Retardation Gene and Proteinmentioning
confidence: 99%
“…Much of the information that specifies the transcriptional program of a gene is encoded in its DNA sequence. These cis-acting sequences include enhancers, silencers, proximal promoter regions, core promoters, and boundary/insulator elements (see, for example : Struhl, 1987;Weis and Reinberg, 1992;Smale, 1994Smale, , 1997Smale, , 2001Blackwood and Kadonaga, 1998;Bulger and Groudine, 1999;Butler and Kadonaga, 2002;West et al, 2002). Enhancer and silencer elements contain recognition sites for a variety of sequence-specific DNA-binding factors, and can act from long distances (such as tens of kbp) from the transcription start site.…”
Section: Regulation Of Transcription By Rna Polymerase IImentioning
confidence: 99%
“…The exact responsible sites downstream from ET-1 stimulation remain unknown, since previous studies have not revealed any elements involved in negative regulation. TATA-less promoters, including integrin , have a consensus sequence of an initiator element near each transcription initiation site critical for positioning RNA polymerase II (29). The initiator element, on the other hand, is also under the control of the potent transcription inhibitory effect of an immediate early response gene, cMyc (30).…”
Section: Discussionmentioning
confidence: 99%